2001
DOI: 10.1614/0890-037x(2001)015[0137:vmtpah]2.0.co;2
|View full text |Cite
|
Sign up to set email alerts
|

Virginia Market-Type Peanut (Arachis hypogaea) Cultivar Tolerance and Yield Response to Flumioxazin Preemergence1

Abstract: Field studies were conducted in 1996 and 1997 to evaluate response of eight peanut cultivars to flumioxazin applied preemergence (PRE) at 71 g ai/ha. Peanut cultivars evaluated include ‘NC 12C’, ‘NC 7’, ‘VAC 92R’, ‘NC-V 11’, ‘NC 10C’, ‘AT VC 1’, ‘NC 9’, and the experimental breeding line ‘N9001OE’. Visible injury 3 wk after planting in 1996 was 3% or less regardless of cultivar. In 1997, all cultivars were injured 15 to 28% with flumioxazin PRE, except VC 1, which was injured 45%. No visible injury was observe… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

9
30
0
3

Year Published

2003
2003
2023
2023

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 31 publications
(42 citation statements)
references
References 8 publications
9
30
0
3
Order By: Relevance
“…Injury observed was stunting; however, the peanuts quickly recovered. This response is consistent with previous research where runner-and Virginia-type peanut injury from flumioxazin was transient and did not affect yields (Main et al 2003;Wilcut et al 2001).…”
Section: Resultssupporting
confidence: 92%
See 1 more Smart Citation
“…Injury observed was stunting; however, the peanuts quickly recovered. This response is consistent with previous research where runner-and Virginia-type peanut injury from flumioxazin was transient and did not affect yields (Main et al 2003;Wilcut et al 2001).…”
Section: Resultssupporting
confidence: 92%
“…Injury, with possible yield losses, from flumioxazin and norflurazon can be expected. However, flumioxazin injury is possibly caused by cool wet weather (Askew et al 1999;Main et al 2003;Wilcut et al 2001;Yoshida et al 1991), which may be avoided by a later planting date. Other research has demonstrated that flumioxazin provides growers with a good PRE herbicide option for dry peanut (Eastin et al 1993;Grichar and Colburn 1996;Main et al 2000;Wilcut and Cranmer 1997).…”
Section: Resultsmentioning
confidence: 99%
“…In previous research, only POST applications of chlorimuron had an influence on the incidence of TSWV in peanut (Prostko et al 2009). In other peanut research, applications of diclosulam (PPI), flumioxazin (PRE), imazapic (POST), paraquat (POST), and 2,4-DB (POST) did not affect the incidence of TSWV (Bailey et al 2000;Faircloth and Prostko 2010;Tubbs et al 2010;Wilcut et al 2001). The mechanism of how certain herbicides influence TSWV in peanut has not yet been discovered.…”
Section: Resultsmentioning
confidence: 99%
“…Lima et al (1999) relatam que resíduos de flumioxazin no solo afetaram seriamente o acúmulo de matéria seca em plantas de pepino. Wilcut et al (2003) constataram que a espécie Arachis hypogaea apresentou crescimento reduzido ao ser implantada cinco semanas após a aplicação de 20 g ha -1 de flumioxazin.…”
Section: Introductionunclassified